OUTBURST ACTIVITY OF THE DWARF NOVA AB DRACONIS - Smykov, V. P.; Shakun, L. I. (Одеські астрономічні публікації, 2017)
Two different stages of the outburst activity were found cyclically replacing each other every 6 yr. Mean outburst cycle is 13.1327d (1943-1991). Photometric period is P = 0.1529581d. Amplitude increases with decreasing brightness.